2004
DOI: 10.1118/1.1707755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the imaging properties of an amorphous selenium‐based flat panel detector for digital fluoroscopy

Abstract: The imaging performance of an amorphous selenium (a-Se) flat-panel detector for digital fluoroscopy was experimentally evaluated using the spatial frequency dependent modulation transfer function (MTF), noise power spectrum (NPS), and detective quantum efficiency (DQE). These parameters were investigated at beam qualities and exposures within the range typical of gastrointestinal fluoroscopic imaging (approximately 0.1 - 10 microR, 75 kV). The investigation does not take into consideration the detector cover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 22 publications
1
69
0
Order By: Relevance
“…5,6 Evaluations of direct-conversion a-Se based detector with 150 µm pitch have shown a limiting resolution of approximately 6 cycles/mm. 6,9 Characterization of a MAF employing a 300 µm thick CsI:Tl scintillator coupled to a CCD with 35 µm pitch via a light image intensifier and fiberoptic taper showed a limiting resolution of 4 cycles/mm. 11 The observed 10% MTF of ∼12 cycles/mm with the investigated detector in the SPC mode compares favorably with the added advantage of effectively eliminating electronic noise through appropriate selection of the energy threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Evaluations of direct-conversion a-Se based detector with 150 µm pitch have shown a limiting resolution of approximately 6 cycles/mm. 6,9 Characterization of a MAF employing a 300 µm thick CsI:Tl scintillator coupled to a CCD with 35 µm pitch via a light image intensifier and fiberoptic taper showed a limiting resolution of 4 cycles/mm. 11 The observed 10% MTF of ∼12 cycles/mm with the investigated detector in the SPC mode compares favorably with the added advantage of effectively eliminating electronic noise through appropriate selection of the energy threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Image intensifierbased systems were the mainstay for several decades, but suffered from veiling glare, distortions, and degradation of image quality with time. Hence, indirect conversion CsI:Tl scintillator coupled amorphous silicon (a-Si) flat-panel detector, [4][5][6] tiled large-area charge-coupled devices (CCDs) coupled to CsI:Tl scintillator, 7,8 and direct conversion amorphous selenium (a-Se) photoconductor-based flat-panel detector 9 were developed. Current generation of interventional C-arm systems utilize flat-panel detectors with pixel pitch ranging from 143 to 200 µm, depending on the manufacturer and the intended application.…”
Section: Introductionmentioning
confidence: 99%
“…With N s = 128 and further increase in t p to 3.4 S, the first frame lag is 4.3%, which is within the range of lag values measured in AMFPIs. [13][14][15] Further reduction in lag could be realized by incorporating the charge clearance procedure described in Sec. IV D 2.…”
Section: Ivd3 Lag Reduction In Saphirementioning
confidence: 99%
“…In a fluoroscopic system, lag is usually required to be less than 10% after the first frame, 12 and the values measured from most indirect active matrix FPIs ͑AM-FPIs͒ are between 2% and 10% depending on the x-ray exposure and detector operation. [13][14][15] The temporal performance of CsI ͑Tl͒ has been studied extensively for indirect AMFPI. It was found that the lag due to the afterglow of the CsI ͑Tl͒ is ϳ0.1% after 5 ms, and the typical values of ghosting are 1% and 3% at the exposure levels of 1 and 10 mGy, respectively.…”
mentioning
confidence: 99%
“…1 The current leading technology in digital x-ray systems in terms of image quality and dose to the patient is based on large area active matrix flat panel imagers ͑AMFPIs͒. 2 While AMFPIs provide excellent image quality and increased functionality over traditional film-screen systems, they are very expensive and are therefore used primarily for specialized procedures such as fluoroscopy, 3 cone-beam computed tomography ͑CT͒, 4 and digital tomosynthesis. 5 The most commercially successful digital radiographic x-ray systems are cassette-based computed radiography ͑CR͒ systems.…”
Section: Introductionmentioning
confidence: 99%